Identification of training needs among secondary school esl teachers in Perak Tengah - Baharudin, Bin Mat Isa (1997)
Currently there is no written policy for the training of English as a Second Language (EL) secondary school teachers in Perak Tengah. Training was traditionally done on an ad hoc basic and was practically based on the percept of the trainers. This study was undertaken to identify the perceived training need of 52 practising ESL teachers, as perceived by themselves, in the following categories : knowledge, teaching methods and strategies, classroom based skills and organizational and management skills.